Road pricing : technologies, economics and acceptability - Walker, John (The Institution of Engineering and Technology, 2018)
Road pricing is increasingly being implemented around the world to combat congestion, curb carbon emissions, compensate for falling revenues from fuel duty, improve the efficiency of the existing transport infrastructure, and fund new transport projects. This book outlines some of the economic theory behind these schemes.
Keywords: Congestion pricing.; Roads -- Finance.; Electronic Road Pricing System.; Toll roads.; Transportation and state.; elektronické knihy; electronic books